1999
DOI: 10.1159/000015321
|View full text |Cite
|
Sign up to set email alerts
|

The influence of interstitial telomeric sequences on chromosome instability in human cells

Abstract: Although most telomere repeat sequences are found at the ends of chromosomes, some telomeric repeat sequences are also found at intrachromosomal locations in mammalian cells. Several studies have found that these interstitial telomeric repeat sequences can promote chromosome instability in rodent cells, either spontaneously or following ionizing radiation. In the present study we describe the extensive cytogenetic analysis of three different human cell lines with plasmids containing telomeric repeat sequences … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
1

Year Published

2001
2001
2011
2011

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 28 publications
2
16
1
Order By: Relevance
“…It has been suggested that ITSs are preferential sites of breakage (Bertoni et al 1994(Bertoni et al , 1996Desmaze et al 1999); the conclusions derived from the present work support instead the hypothesis that the short primate ITSs are relics of ancient breakage within fragile sites rather than fragile sites themselves.…”
Section: Discussioncontrasting
confidence: 50%
“…It has been suggested that ITSs are preferential sites of breakage (Bertoni et al 1994(Bertoni et al , 1996Desmaze et al 1999); the conclusions derived from the present work support instead the hypothesis that the short primate ITSs are relics of ancient breakage within fragile sites rather than fragile sites themselves.…”
Section: Discussioncontrasting
confidence: 50%
“…We performed TRF1 and TRF2m ChIP-qPCR in the SNG28 human squamous carcinoma cell line. This cell line contains an artificially integrated 800-bp telomeric sequence in the middle of the long arm of chromosome 4 (named 4qITS) [26,30], which serves as a positive control for the immunoprecipitations. We observed a clear TRF1 and TRF2 enrichment for five out of five identified TRF binding sites and also of the 4qITS sequence ( Figure 3).…”
Section: Validation By Chip-qpcrmentioning
confidence: 99%
“…In human chromosomes, the presence of ITR induces chromosome instability, resulting in spontaneous or artificial chromosome rearrangement (Park et al 1992, Boutouil et al 1996, Slijepcevic et al 1996, Desmaze et al 1999. Ames and Mitra (1968) and Hanmoto et al (2003) reported that the subdistal positions of the long arms in both 1g and 2g chromosomes of H. gracilis are the breakage points by maleic hydrazide treatment and by ionizing radiation, respectively.…”
Section: Correlation Between Itrs Site and Chromosome Instabilitymentioning
confidence: 99%